2004
DOI: 10.1207/s15374424jccp3303_10
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Adolescent Mothers' History of Antisocial Behavior to Child Conduct Problems and Social Competence

Abstract: We examined the extent to which maternal antisocial behavior (ASB) is directly related to child conduct problems and social competence and assessed the potential mediating role of negative parenting. The sample included 93 adolescent mothers and their children (44 boys, 49 girls). Mothers retrospectively reported about their ASB since the child's birth, through Grade 2. Negative parenting was coded during a parent-child interaction task (PCIT) at Grade 2. Teachers assessed child outcomes at Grade 3. Maternal A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 58 publications
2
27
1
Order By: Relevance
“…Maternal psychopathology maintains a direct association with ASB in children. These results are consistent with other studies on parental mediation, which suggest that the direct effect of maternal psychopathology persists despite the inclusion of mediators [8,22]. This direct link may suggest that alterations in the mother's psychological functioning (changes in emotions or mood) can directly affect children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Maternal psychopathology maintains a direct association with ASB in children. These results are consistent with other studies on parental mediation, which suggest that the direct effect of maternal psychopathology persists despite the inclusion of mediators [8,22]. This direct link may suggest that alterations in the mother's psychological functioning (changes in emotions or mood) can directly affect children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, negative parenting partially mediated the relationship between maternal ASB and conduct problems in children [8].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A handful of recent studies have found significant relationships between fathers' (Smith and Farrington 2004), mothers' (Rhule et al 2004), and both parents' (Blazei et al 2008;Jaffee et al 2003) antisocial behaviors and children's externalizing problems in early to middle childhood. One primary limitation is a lack of research assessing a potential link between parents' antisocial behaviors and children's internalizing behaviors (see Marmorstein and Iacono 2004 for an example with adolescents).…”
Section: Direct Intergenerational Transmission Of Antisocial Behaviorsmentioning
confidence: 99%